PERBEDAAN EFEKTIVITAS CHLORHEXIDINE GLUKONAT 0,2% DENGAN TEH HIJAU (CAMELLIA SINENSIS) TERHADAP JUMLAH PORPHYROMONAS GINGIVALIS - Devi Dwipriastuti; R. Rama Putranto; Welly Anggarani (ODONTO : Dental Journal, 2017)
Background: Periodontitis is a periodontal inﬂammation caused by plaque that contains pathogens, Porphyromonas gingivalis is one of them. Chlorhexidine therapy used to reduce the number of pathogenic bacteria causing periodontitis. Green tea contains polyphenols such as epigallocatechin-3-gallic as antibacterial agent that can kill the bacteria Porphyromonas gingivalis. This study aims to determine diﬀerences in the eﬀectiveness of chlorhexidine gluconate 0.2% with green tea (Camellia sinensis) various concentrations to decrease the amount of bacteria Porphyromonas gingivalis.Method: This research was experimental with post test only design. Method used in antibacterial test was a drop plate misra. The experimental group consisted of six groups: chlorhexidine gluconate 0.2% and green tea group with a concentration of 100%, 75%, 50%, 25% and 12.5%. minimum bactericidal concentrations againts Porphyromonas gingivalis was evidenced by counting the number of colonies that formed on agar. Analysis data was using One Way ANOVA continued by Post hoc tests Tamhane.Result: The results showed that chlorhexidine gluconate 0.2% with green tea eﬀective to decrease the amount of bacteria Porphyromonas gingivalis(ANOVA p <0.05). The results between the groups showed green tea 100%, 75% and 25%, have same eﬀect compared to chlorhexidine gluconate 0.2% in reducing Porphyromonas gingivalis.Conclusion: In this experiment showed that chlorhexidine gluconate 0.2% and green tea extract 100%, 75%, 50%, 25% and 12.5% were able to decrease the amount of Porphyromonas gingivalis.